2019
DOI: 10.1186/s11556-019-0212-7
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for assessing motor performance in individuals with dementia: suggestions of an expert panel – a qualitative approach

Abstract: Background Recommendations for assessing motor performance in individuals with dementia (IWD) are rare, and most existing assessment tools previously applied in IWD were initially developed for healthy older adults. However, IWD and their healthy counterparts differ in motor and cognitive capabilities, which needs to be considered when designing studies for this population. This article aims to give recommendations for motor assessments for IWD and to promote standardisation based on a structured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 81 publications
1
14
0
Order By: Relevance
“…more verbal and physical cueing in the walk tests (Table 4). A recent consensus reached by a panel of experts working in the care of people with dementia has stated that physical performance assessments should be tailored for the specific characteristics of dementia, and external cues are necessary during assessments (Trautwein et al, 2019). Our findings have provided further support to the consensus that systematic cueing should be an integral part of the testing protocols of the walk tests for older adults with dementia in order to obtain accurate assessment results from this group.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…more verbal and physical cueing in the walk tests (Table 4). A recent consensus reached by a panel of experts working in the care of people with dementia has stated that physical performance assessments should be tailored for the specific characteristics of dementia, and external cues are necessary during assessments (Trautwein et al, 2019). Our findings have provided further support to the consensus that systematic cueing should be an integral part of the testing protocols of the walk tests for older adults with dementia in order to obtain accurate assessment results from this group.…”
Section: Discussionsupporting
confidence: 72%
“…Poor short-term memory and executive function, difficulties to follow instructions, and psychological and behavioral symptoms are the common clinical features found in people with dementia that can reduce their capacities to complete physical performance tests (Rockwood et al, 2000). Providing systematic verbal and physical cues has been shown effective in facilitating the performance of people with dementia in physical performance tests (Nordin et al, 2006;Ries et al, 2009;Tappen et al, 1997;Trautwein et al, 2019). Our previous study has demonstrated that providing systematic cues could maximize the consistency of the performances of older adults with dementia in the walk tests (Chan and Pin, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Feasibility of the motor assessments were discussed with an international expert panel before the conduct of this study. Furthermore, a standardized testing procedure was developed by the expert panel (Trautwein et al, 2019). Subsequently, the applied test battery has been checked for feasibility in IWD.…”
Section: Discussionmentioning
confidence: 99%
“…The strengths of the study include the emphasis on high-quality methods and a detailed reporting of our methods and findings [ 53 ]. Of note, we had a large sample size of over 300 individuals with mild to moderate dementia, our assessments were deemed adequate for IWD by an expert panel [ 87 ], and our MEP was specifically tailored to fit the needs and characteristics of IWD (please refer to [ 53 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Third, the assessments to determine motor performance used in this study are widely used in research but have not been specifically developed for IWD. Even though we intensively discussed the adequateness of these assessments during an expert panel [ 87 ] and carefully selected the most appropriate ones, we cannot rule out the possibility that the use of existing assessments not specifically designed for IWD may have led to biased results. For example, these assessments often do not sufficiently take into account fluctuating daily forms and motivational aspects that may play a role when examining IWD.…”
Section: Discussionmentioning
confidence: 99%